2000
DOI: 10.4049/jimmunol.164.5.2644
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of IL-18 Reduces Neutrophil Tissue Accumulation and Protects Mice Against Lethal Escherichia coli and Salmonella typhimurium Endotoxemia

Abstract: In addition to stimulating IFN-γ synthesis, IL-18 also possesses inflammatory effects by inducing synthesis of the proinflammatory cytokines TNF and IL-1β and the chemokines IL-8 and macrophage inflammatory protein-1α. We hypothesized that neutralization of IL-18 would have a beneficial effect in lethal endotoxemia in mice. IL-1β converting enzyme (ICE)-deficient mice, lacking the ability to process mature IL-18 and IL-1β, were completely resistant to lethal endotoxemia induced by LPS derived from either Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
151
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(169 citation statements)
references
References 42 publications
15
151
2
1
Order By: Relevance
“…12,14 The present study also showed that mRNA levels of MIP-2, KC, and ICAM-1 were significantly induced by LPS challenge. Netea et al showed that IL-18 induced LPS-mediated accumulation of neutrophils by increasing MIP-2 expression in the lung.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…12,14 The present study also showed that mRNA levels of MIP-2, KC, and ICAM-1 were significantly induced by LPS challenge. Netea et al showed that IL-18 induced LPS-mediated accumulation of neutrophils by increasing MIP-2 expression in the lung.…”
supporting
confidence: 53%
“…Netea et al showed that IL-18 induced LPS-mediated accumulation of neutrophils by increasing MIP-2 expression in the lung. 12 However, our results showed that IL-18 did not significantly affect MIP-2 (CXCL2) mRNA expression, whereas IL-18 induced ICAM-1 mRNA expression in the lung. One reason for this discrepancy is the peak time of these molecules.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…2,3 This is likely due to the lack of mature IL-18 in these mice, since protection from LPS-induced lethality is not observed in IL-1b-deficient animals, while neutralization of IL-18 confers complete resistance to lethal endotoxemia. 5,6 Is caspase-12 involved in responses to infection and inflammation? Contrary to caspase-1, but similar to caspase-11, coexpression of caspase-12 with the precursor of the proinflammatory cytokine interleukin-1b (pro-IL-1b) does not result in the maturation of pro-IL-1b 1 (and Lamkanfi et al, unpublished results).…”
Section: Is Caspase-12 Implicated In Inflammation?mentioning
confidence: 99%
“…In addition to stimulating IFN-γ synthesis, IL-18 also exhibits inflammatory effects and its neutralisation protects mice infected with ST against the effect of LPS and TNF [22]. We have found high levels of IL-18 in ileum lavages but not in the plasma of infected piglets.…”
Section: Discussionmentioning
confidence: 61%